Hydrodynamism and its influence on the density of the decorator crab Microphrys bicornutus (Mithracidae) on intertidal rocky shores from a subtropical region - Blanco, Camila G. [UNESP]; Gusmao-Junior, Joao B. L. [UNESP]; Christofoletti, Ronaldo A.; Costa, Tânia Marcia [UNESP] (Taylor & Francis As, 2011)
Hydrodynamism is an environmental stressor on marine communities with effects on populations of intertidal organisms. Microphrys bicornutus is a crab species associated with secondary substrates on rocky shores and little is known about its population dynamics and its relation to the shore hydrodynamics. The aim of this study is to describe the population structure of Microphrys bicornutus on intertidal rocky shores from the north coast of the São Paulo State, Brazil, and the influence of wave exposure on the density of this decorator crab. There was a greater density of M. bicornutus on sheltered than on exposed rocky shores, which is probably due to the hydrodynamic influence on M. bicornutus populations on rocky shores: directly ( by the physical stress caused by wave impact) and indirectly ( by determining the dominance of the secondary substrate) acting on the density of these crabs. Our results also suggest a vertical distribution of juveniles and adults, where the juveniles might be more abundant on the infralittoral fringe and, thus, more influenced by hydrodynamism than adults in the infralittoral.
Keywords: Brachyura; epifauna; macroalgae beds; mussel beds; population dynamics